1997
DOI: 10.1042/cs0920473
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low-Density Lipoprotein and High-Density Lipoprotein on Blood Viscosity Correlate with their Association with Risk of Atherosclerosis in Humans

Abstract: 1. Increased blood or plasma viscosity has been observed in almost all conditions associated with accelerated atherosclerosis. Cognizant of the enlarging body of evidence implicating increased viscosity in atherogenesis, we hypothesize that the effects of low-density lipoprotein and high-density lipoprotein on blood viscosity correlate with their association with risk of atherosclerosis. 2. Blood viscometry was performed on samples from 28 healthy, non-fasting adult volunteers using a capillary viscometer. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 12 publications
2
67
0
Order By: Relevance
“…This supports the concept that an increase in LDL-Chol is a risk factor for atherosclerosis. 25 Other Authors have hypothesized that LDL-Chol can modulate blood viscosity by a mechanism similar to the one operated by fibrinogen. 26 In this study we observed a reduction in the AI % and an increase in the AI t 1 2 in obese patients who lost weight after the application of adjustable gastric banding.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the concept that an increase in LDL-Chol is a risk factor for atherosclerosis. 25 Other Authors have hypothesized that LDL-Chol can modulate blood viscosity by a mechanism similar to the one operated by fibrinogen. 26 In this study we observed a reduction in the AI % and an increase in the AI t 1 2 in obese patients who lost weight after the application of adjustable gastric banding.…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipoproteins concentration may be another shared mechanism linking blood viscosity [3,39] and elevated 1-h post-challenge plasma glucose [33]. Low HDL levels have been associated with an elevated blood viscosity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accrued suggesting that subjects with a 1-h plasma glucose concentration during an oral glucose tolerance test (OGTT) [155 mg/dl (8.6 mmol/l) are at increased risk of type 2 diabetes among those who have NGT [28][29][30][31]. Remarkably, subjects with 1-h postchallenge plasma glucose [155 mg/dl are characterized by a cluster of cardio-metabolic abnormalities such as insulin resistance [32], pro-atherogenic lipid profile [33], hepatic steatosis [34], carotid atherosclerosis [35], vascular stiffness [36], and left ventricular hypertrophy [37], and cardiac autonomic imbalance [38] which in turn have been inked to increased blood viscosity [1,3,[7][8][9][10][11]. The degree to which 1-h post-load plasma glucose [155 mg/dl is associated with blood viscosity remains unsettled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high-fat diets change blood cell-related characteristics, increase total cholesterol and Low Density Lipoprotein-cholesterol (LDL-c), and decrease HDL-c. On the other hand, low levels of fatty acids increase blood viscosity and the risk of atherosclerosis 18 . Blood viscosity increases when hematocrit, number of circulating erythrocytes, or cell volume increases.…”
Section: Introductionmentioning
confidence: 99%